2005
DOI: 10.1017/s0317167100004200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Stringency Greatly Improves Mutation Detection in Rett Syndrome

Abstract: Rett Syndrome (RTT, OMIM 312750) is characterized by onset in the first 18 months of life of slowing and arrest of neurodevelopment paralleled with a loss of communication and motor skills acquired to that point. Purposeful hand movements are replaced by a semi-continuous hand-washing stereotype. Social interaction with the family disintegrates, resembling autistic withdrawal and, with the passage of time, a picture of profound mental retardation emerges. 1 However, depending on mutation location and extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In Patient 1, we detected a novel mutation, c.1A > T that disrupts the initiation codon, changing it to a leucine. We reported on the identification of this mutation previously [Gauthier et al, 2005]. In silico analysis of translation initiation using NetStart predicts that translation of MeCP2_e1 would be ablated, but without any negative affect on translation of MeCP2_e2.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In Patient 1, we detected a novel mutation, c.1A > T that disrupts the initiation codon, changing it to a leucine. We reported on the identification of this mutation previously [Gauthier et al, 2005]. In silico analysis of translation initiation using NetStart predicts that translation of MeCP2_e1 would be ablated, but without any negative affect on translation of MeCP2_e2.…”
Section: Resultsmentioning
confidence: 95%
“…All mutations localized to exon 1 reported until recently have been either small insertions or deletions or large deletions removing the entire exon. These three single base pair changes are the first point mutations to be reported in exon 1 of the MECP2 gene [also see Gauthier et al, 2005]. The c.1A > T and c.1A > G mutations alter the initiation codon, which would mostly likely result in absent translation of MeCP2_e1.…”
Section: Discussionmentioning
confidence: 97%
“…However, subsequently, several classic Rett patients were identified with mutations affecting the start codon in exon 1 (Gauthier et al, 2005;Saunders et al, 2009). Levels of mRNA for MeCP2-E1 and E2 were unaffected, and peripheral blood lymphocytes were still positive for MeCP2 antibodies, and thus presumably only able to generate the MeCP2-E2 protein (Gianakopoulos et al, 2012).…”
Section: Mecp2 N-terminal Mutationsmentioning
confidence: 99%
“…Autism is a neurodevelopmental disorder characterized by deficits in communication and reciprocal social interaction accompanied by repetitive/stereotyped behaviors and/or restricted areas of interest. Autism disproportionately affects males, and some researchers have therefore searched for the involvement of X‐linked loci [Jamain et al, 2003; Gauthier et al, 2005; Gong et al, 2008], including searches for MECP2 mutations in cases of idiopathic autism [Lam et al, 2000; Vourc'h et al, 2001; Beyer et al, 2002; Carney et al, 2003; Lobo‐Menendez et al, 2003; Coutinho et al, 2007]. These studies demonstrated that mutations in the coding region of MECP2 are a rare cause of idiopathic autism.…”
Section: Autism and Mecp2 Duplication Syndromementioning
confidence: 99%